Identification processes in cultural and educational space of the university as a source of the nascence of educational values - Olesia Smolinska; Khrystyna Dzyubynska (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
Values, especially educational, are produced institutionally. That is why the study of their content without analyzing the origin and methods of generating leads to fragmentary research. University, in fact, is this public institution in the cultural and educational space, where the values of higher education that correspond to current political and economic status of society and have historical and cultural nature, are formed, circulate, develop and freeze. The process of generating values is simultaneous with the process of identification, thus, different groups of values, differences in identification should be taken into account and, particularly those typical of the university, which define its characteristics, including self characteristics. They include temporal, physical/body, social-class self-identity; however, beyond the scientific analysis, there are gender, national and other kinds, although they are no less significant to the Ukrainian reality. An important conclusion is that that there is a causal relationship between the self-identity of the university and origin and evolution of educational values in its cultural and educational space that prove the influence of university education on the development of society, in particular - as regards putting forward priorities and forming goals.